Teaching Second Language Learners (Eurasian Journal of Learning and Academic Teaching, 2023)
This article explores the key factors and considerations in teaching second language learners, emphasizing the importance of cultural sensitivity, language acquisition theories, and differentiated instruction. Using a mixed-methods approach, the study investigates the relationship between instructional approaches and learners' language proficiency levels. The findings contribute to the discourse on best practices in teaching second language learners, providing insights for educators and policymakers to enhance language learning outcomes and promote linguistic diversity in educational settings.